The Relevance Of Election Organizing Institutions In Resolving Presidential Election Disputes - Rohadi, Ahmad Nur; Prasetyoningsih, Nanik (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The General Election Commission (KPU) is an election organizing institution that is national, permanent, and independent in organizing elections. Holding direct presidential elections is a democratic instrument to create a more democratic government and a step toward realizing people's sovereignty. In this research activity, the type of research used is normative juridical research (legal research), which prioritizes library research. However, along the way, various accompanying problems arose. Ultimately, these things must be considered challenges and part of the maturation process to create a more mature state government. As explained above, the various disputes in the final stages of voting for the elected candidate pairs in the Presidential Election show that we still have a lot of democratic agenda that needs to be resolved regarding regulations, institutions, and law enforcement. Thus, the disputes that occur should become part of the election maturation process as the period changes.